Trends in overweight and obesity among reproductive-age women in Bangladesh: Analysis of nationally representative surveys over a decade - Urby Saraf Anika; Md. Abdur Rafi; Md. Shajedur Rahman Shawon; Md. Golam Hossain (PLoS ONE, 2026)
Background Overweight and obesity are emerging public health concerns in Bangladesh, contributing to the rising burden of non-communicable diseases. We aimed to examine trends in prevalence of overweight and obesity among reproductive-age women in Bangladesh over the past decade and assess socioeconomic inequalities in their distribution. Methods We analyzed nationally representative data from four rounds of the Bangladesh Demographic and Health Survey (BDHS) conducted in 2011, 2014, 2017–18, and 2022, including a total of 60,921 women aged 15–49 years. Body mass index (BMI) was classified using Asian-specific cut-offs. Prevalence estimates of overweight and obesity were calculated for each survey year and stratified by age, residence, educational attainment, and wealth quintile. Log-linear regression was used to estimate annual percentage changes (APC) in overweight and obesity. Socioeconomic inequality was quantified using concentration curves and Erreygers-corrected concentration indices (CIX). Results Overall prevalence of overweight and obesity increased from 13.1% in 2011 to 18.7% in 2022 (APC 3.1%), and 17.7% to 36.6% (APC 6.8%), respectively. Rural women experienced faster relative increases in both overweight (APCs 4.4% vs 1.1%).and obesity (APCs 9.2% vs 4.3%) compared with urban women. Women in the poorest and poorer wealth quintiles showed the largest APCs for obesity (14.2% and 14.1%, respectively). The CIX for overweight declined from 0.098 to 0.031, and for obesity from 0.200 to 0.141, indicating a modest reduction in inequality concentrated among wealthier groups over time. Conclusions Overweight and obesity are increasing rapidly among reproductive-age women of Bangladesh, with faster rises among rural and lower-income groups. Policies and interventions should address both overall prevalence and shifting socioeconomic patterns to reduce the future burden of non-communicable diseases.